The Role of Civil Society in the European Integration Process in Kosovo: EU Mechanisms and Instruments for NGO Sector Development - Kastrati, Ardian (European Scientific Journal, ESJ, 2017)
European integration is one of the most demanding processes for Kosovo institutions and society. While citizens of Kosovo overwhelmingly support membership in the European Union, assessment reports specify that Kosovo and its institutions still need serious reform to achieve this goal. The integration process offers mechanisms that civil society namely NGO sector can use in order to monitor and give direct contribution for this process, which could also impact to transform Kosovo institutions and society. The Annual Progress Report of the European Commission requires from governments and institutions of countries aspiring for integration to the EU to pursue sound governance practices that allow civil societies to have an impact on policy and decision-making processes. Relying on this requirement, NGOs can use the process as a way to shape the organization and function in their society and institutions. At this stage the role of Kosovo NGO’s whose focus is political activism that tends to increase demands for democratic participation in the political system is more than needed. These NGO’s apart from monitoring role towards the Government, they can become one of the main partners for EU Integration Process, especially to the European Commission (EC). The aim of this paper is to analyze the role of NGO’s as part of civil society in the whole process of EU integration and current possibilities for improving their capacities and contributions towards the public policy and decision making process.